A comparative study on the corrosion of gathering pipelines in two sections of a shale gas field. (March 2021) - Jiang, Xiu; Xu, Ke; Guan, Xiaorui; Qu, Dingrong; Song, Xiaoliang; Zhang, Quan; Yu, Chao; Hua, Jing
Highlights: Comparative analysis of shale gas pipeline failures in two sections was studied. Serious failures occur after 1 year in one section, but none are in the other section. Pitting corrosion caused by MIC and under-deposit corrosion dominates failures. Flow characteristics leads to the notable failure difference between two sections. Abstract: Sixty-eight pipeline failures occurred at the gas-gathering stations located in the southwestern section of a shale gas field, whereas no failures were reported for the corresponding pipelines in the northeastern section of the same field. This paper reports a comprehensive comparative analysis of the pipeline failures in the two sections of the field. Failure case statistical analyses, environmental media inspection, matrix materials examination, macro- and microscopic morphologies observation, corrosion products detection, and CFD analysis were carried out to understand the significant difference between two sections in terms of pipeline failures. Our analyses demonstrate that an abundance of bacteria were present in the water produced in both sections of the shale gas field. Most of the pipeline failures occurred after approximately 1 year. The number of failures tended to increase significantly over 3 years of service. Pitting corrosion at the bottom of pipelines, erosion-corrosion and weld corrosion at elbows were identified as the key contributing causes of the pipeline failures. Microbiologically influenced corrosion (MIC) and under-deposit corrosion was the root cause of sixty-six percent of pitting corrosion failures at the bottom of the pipelines. Erosion-corrosion and weld corrosion at elbows totally accounted for 34% of failures. Flow characteristics in the pipelines were finally determined to be one of the underlying causes of the notable difference in the corrosion behavior of the pipelines in the two sections. Pertinent countermeasures have been proposed in this paper. It is hoped that this work will help corrosion engineers involved with designing, monitoring, and managing pipelines to improve their designs and subsequent monitoring and treatment of pipelines to prevent premature failure of gathering pipelines in shale gas fields.